Die Briefe des Ignatios von Antiochia Motive, Strategien, Kontexte - Möllendorff, Peter von; Bauer, Thomas Johann (Millennium-Studien / Millennium Studies, 2018)
The letters preserved under the name of Ignatios of Antiochia remain a contentious topic to this day among scholars of early Christianity. The essays collected in this volume discuss issues about their origins and cultural context, their function and intention, their theological content and transmission, and their form and composition as an epistolary collection.